Expanding the absorption bandwidth with two-layer graphene metamaterials in gigahertz frequency range - Viet, Ngo Nhu; Lam, Vu Dinh; Tung, Bui Son; Khuyen, Bui Xuan; Son, Pham Thanh; Anh, Nguyen Hai; Hai, Nguyen Phon; Tung, Do Khanh; Chi, Do Thuy (Communications in Physics, 2024)
This work investigates the design and performance of a bilayer graphene metamaterial absorber operating in the GHz region. We initially analyzed a single-layer metamaterial absorber composed of a conductive ink graphene structure on a FR-4 dielectric substrate backed by a continuous copper sheet. Subsequently, a second graphene-FR4 layer of identical dimensions was added to create a bilayer structure. While the number of absorption peaks increased, they remained isolated, failing to achieve the desired broadband effect. To overcome this limitation, we explored graphene layers with varying surface resistances. Our findings demonstrate that the bilayer graphene metamaterial absorber achieves an absorption exceeding 90% with a remarkable bandwidth of 9.1 GHz, spanning frequencies from 6.21 GHz to 15.31 GHz. This significant bandwidth expansion is attributed to the synergistic interactions and contributions between the graphene and metal layers within the structure. To gain a deeper understanding of the underlying absorption mechanism, we investigated the surface current distribution, the impact of conductivity, and the individual contributions of each layer. Additionally, we examined the influences of both incident angle and polarization angle on the absorption performance of the proposed bilayer MA. These comprehensive analyses provide valuable insights into the mechanisms responsible for the enhanced absorption observed in multilayer metamaterial structures. Our work holds relevance and might be useful to develop electromagnetic wave shielding technologies and devices operating in the GHz frequency range.